Knowledge and Preventive Practice of Pulmonary Tuberculosis Among Tuberculosis Patients in Chitwan District - Kalakheti, Kamal; Poudyal, Jiwan Kumar; Upadhyay, Hari Prasad; Adhikari, Alina; Adhikari, Sudip; Sedain, Prativa (Journal of National Heart and Lung Society Nepal, 2022)
Background: Tuberculosis (TB) is one of the world’s most serious infectious diseases caused by Mycobacterium tuberculosis. Tuberculosis typically attacks the lungs, but can also affect other parts of the body. Methods: An analytical cross-sectional study was conducted patients who were suffering from tuberculosis and taking Anti-TB medicine from different DOTS center of Chitwan District during the 22nd August to 3rd September 2021. Data was analyzed using descriptive and inferential statistical tools in SPSS-20. p-value <0.05 was considered as statistically significant. Results: Out of 285 respondents regarding age majority (41.8%) of respondents belong to the age group of 20–34 years. The mean and SD of age was 42.77±1.019 years. More than 60% respondents had good level of practice on preventive measure. None of the variables was found to be statistically significant. Conclusion: Most of the tuberculosis patients had not good level of knowledge and preventive practices so DOTS center and local government need to make strategy on preventive measure.